Empirical equation for the prediction of run-up due to random waves on beaches fronted by vegetation - Murali, K. (2013)
The run-up due to ocean waves on an open coast and over coastal structures is an essential parameter in their planning, design and effectiveness in protecting the shore against natural hazards. Most of the formulae derived in the past for run-up through laboratory studies are for sloping walls exposed to the action of regular and random waves. The presence of vegetation, however, is expected to alter the flow field, thereby resulting in an uncertainty in the application of the existing formulae. A well-controlled experimental program to investigate the effect of vegetation on the run-up due to regular, random and cnoidal waves has been carried out. The details of the parameters adopted for the waves and vegetation, test set-up, experimental procedure, analysis of the results and discussion are reported in this paper.